A New Method for Hybrid Pseudo Random Number Generator - Avaroglu, Erdinc; Tuncer, Taner; Ozer, A. Bedri; Turk, Mustafa (Soc Microelectronics, Electron Components Materials-Midem, 2014)
Powerful cryptographic systems need qualified random numbers. Qualified random numbers need providing good statistical qualities, not predicting and not re-generating. The numbers generated by raw Pseudo Random Number Generators (PRNG) can be predicted when their seed value are detected or the functions used in the system are not complicated enough. Moreover, the stream generated repeats itself after its period is exhausted. Due to these shortcomings mentioned above, raw PRNGs are not suitable for the cryptographic applications. In order to eliminate these shortcomings, by adding an additional input to the raw PRNG system, a hybrid structure is suggested in this study. In the hybrid system, a chaotic attraction in order to generate pseudo random number and a TRNG system having 5 Ring Oscillator (RO) each of which includes 3 inverters as the additional input were used. The random numbers obtained from the suggested hybrid structure were exposed to the NIST 800.22 statistical tests and it is shown that hybrid system can be used in the cryptographic systems.
Keywords: Random Number Generator; Chaotic Attractor; Additional Input; Hybrid Pseudo Random Number Generator